Attitude of Syrian medical specialty trainees toward providing health care services to patients with mental disorders - Hidar Alibrahim; Haidara Bohsas; Sarya Swed; Yasmeen Abouainain; Zain Alabdeen Othman; Yazan Khair Eldien Jabban; Amine Rakab; Wael Hafez; Sherihan fathey; Mohammad Badr Almoshantaf; Mohamad Al Ibrahim; Bisher Sawaf; et al. (BMC, 2023)
Abstract Background The stigma associated with mental diseases in the healthcare system and among healthcare professionals has been identified as a significant barrier to treatment and rehabilitation and to the provision of substandard physical care for persons with mental illnesses. The goal of this study is to assess the attitude of physicians in Syria towards individuals with mental health disorders. Methods An online cross-sectional survey was conducted among phyisicians in Syria to evaluate their attitudes toward patients with mental health disorders and their provided treatment in the time period between August 16 and October 1, 2022. The questionnaire for the study was developed based on previous research, and the inclusion criteria for the sample were all medical specialist trainees from all specialties and residents who had direct contact with people suffering from mental health disorders. The questionnaire was divided into two sections; the first included sociodemographic data on the participants and the second assessed physician's attitudes toward mental illness patients. With the IBM SPSS V. 28.0 package tool (IBM Corporation, Armonk, NY, USA), descriptive and multivariate logistic regression analyses were used to analyze the data. Results 539 medical residents participated in this research; their average age was 26.11 (+- 1.74) years, and 50.27% were males. City residents had the highest stigma score on the third question (2.66 ± 1.06, P value < 0.05) in the 'social distance' domain. The mean stigma scores for these three items in the recovery area were (2.76 ± 1.15, 2.51 ± 0.92, and 3.73 ± 0.83), respectively, for city residents. In the 'social distance' domain, the stigma score of two questions (the first and fourth questions) was associated with the resident's specialty, with dermatology residents having the highest mean score in both questions (mean = 3.6 ± 1.12, 3.43 ± 1.19, respectively). Only the second item in the 'Detection' domain was scored higher (mean = 3.850.81) by surgery residents than other residents. The stigma in the 'Recovery' domain was greatest among dermatology residents (mean = 3.710.94) than among other residents. There was a statistically significant relationship between residency and the Detection stigma scale (p = 0.03, Adj R2 = 0.008). There was a moderate correlation (Adj R2 = 0.048) between the Recovery scale and three of the six predictors (location, marital status, and the number of years living in the current residence). Two demographic factors (country of residence and marital status) were significantly correlated (p0.05) with the Social Responsibility Scale, and the Adjusted R-Squared Value was 0.006. Conclusion Our findings indicate substantial stigma among resident physicians who treat patients with mental illnesses, which might negatively impact both the efficacy of therapy and the phyisician's mental health. It is important to educate medical residents on mental health issues so that they can treat their patients appropriately. It is suggested that mental health concerns be included in the curriculum of residency programs for physicians so that they have adequate perspectives and attitudes about treating these patients.